2024
DOI: 10.1021/acs.jmedchem.3c02412
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin Activator CK-963 Increases Cardiac Contractility in Rats

Scott E. Collibee,
Antonio Romero,
Alexander R. Muci
et al.

Abstract: Novel cardiac troponin activators were identified using a high throughput cardiac myofibril ATPase assay and confirmed using a series of biochemical and biophysical assays. HTS hit 2 increased rat cardiomyocyte fractional shortening without increasing intracellular calcium concentrations, and the biological target of 1 and 2 was determined to be the cardiac thin filament. Subsequent optimization to increase solubility and remove PDE-3 inhibition led to the discovery of CK-963 and enabled pharmacological evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Promising troponin-activating compounds have been developed by investigators at Cytokinetics using a high-throughput assay employing ATPase activity of cardiac myofibrils [102]. These investigators have reported detailed findings in the development of CK-963 and discuss in their recent paper next steps in future clinicals trial with follow-up compounds [102]. Studies reported by He et al [79] provide an example of advances in development of small molecules acting as thin filament activators without PDE III inhibition.…”
Section: Targeting the Troponin Complex Avoiding Pde III Inhibitionmentioning
confidence: 99%
“…Promising troponin-activating compounds have been developed by investigators at Cytokinetics using a high-throughput assay employing ATPase activity of cardiac myofibrils [102]. These investigators have reported detailed findings in the development of CK-963 and discuss in their recent paper next steps in future clinicals trial with follow-up compounds [102]. Studies reported by He et al [79] provide an example of advances in development of small molecules acting as thin filament activators without PDE III inhibition.…”
Section: Targeting the Troponin Complex Avoiding Pde III Inhibitionmentioning
confidence: 99%
“…A myotrope that targeted cardiac troponin, a mechanism distinct from cardiac myosin activators, was envisioned. Cardiac troponin activators have been previously reported, and levosimendan was studied clinically; however, the potent phosphodiesterase-3 (PDE-3) inhibitory activity of levosimendan makes it difficult to assess the pharmacological effect of any potential cardiac troponin activity of this compound. A previous communication outlined a path to find potent, selective cardiac troponin activators devoid of PDE-3 inhibitory activity that show significant increases in cardiac contractility with a shallow pharmacokinetic/pharmacodynamic (PK/PD) profile. This research documents the discovery of the novel, selective cardiac troponin activator, nelutroctiv, devoid of PDE-3 inhibition, with wide a pharmacodynamic window, clear PK/PD relationship, and a preclinical PK profile supporting advancement into clinical development…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac sarcomere activators continue to be explored as potential new treatments in heart failure with reduced ejection fraction (HFrEF). , An area of continued unmet medical need for heart failure patients is in conditions where the contractility of the right ventricle is reduced. For example, congenital heart disease (CHD) is characterized by a range of cardiac birth defects that affect the normal function of the heart .…”
Section: Introductionmentioning
confidence: 99%